Problematika penerapan model pembelajaran berbasis proyek pada pembelajaran menulis teks eksplanasi siswa - Rahmayani, Rizka Dwi; Nursaid, Nursaid (Aksara: Jurnal Bahasa dan Sastra, 2023)
One of language skills that students must to learn is writing. Writing has issues when put into practice. The challenges to the fulfillment of high-quality learning must be overcome. One of them is through picking and organizing a teaching strategy that might spark students' interest in writing. However, there are undoubtedly issues with its application that teachers must deal with. This study was carried out at SMP N 6 Kubung in the West Sumatra Province's Solok Regency. Worksheets for students, project-based learning implementation processes, and teacher learning resources make up the study's data. Teachers, students, and the teaching and learning process are the sources of data.The goal of writing is to describe the issues that teachers encounter. The method adopted is a qualitative descriptive approach, which describes the issues encountered when applying this model. The findings from the research are 1) the planning for implementing the learning model is constrained by funds and facilities; 2) The percentage level of some student activities is low; 3) student motivation and activeness that need to be improved. Applying this strategy can help you learn to create explanatory texts better because it enhances the learning experience. The cooperation of numerous stakeholders is necessary for the successful implementation of this concept. Schools give teachers with the auxiliary resources they require. Teachers must be able to establish trusting bonds with their charges.Keywords: application, model learning, project-based